Effect of Bac-D™ on Hatchability, Conductance, Growth Rate and Feed Conversion on Turkey Poults - Lowman , Zachary; Parkhurst, Carmen (International Journal of Poultry Science, 2014)
The major factor facing the commercial poultry industry today is the cost of feed. Breeding companies have put great emphasis on selecting their lines for rapid growth and low feed to gain to increase the efficiency of production. Even though genetics have made drastic differences in growth parameters, evident from the last 45 years of genetic selection, producers still employ other methods to help birds perform more efficiently including; feed additives, temperature control, incubation, ventilation, hatchery sanitation and egg disinfection. Bac-D™ is a novel disinfectant, which is currently being used as a wound wash for humans and animals. The product utilizes benzalkonium chloride, a well-studied quaternary ammonium compound, which has been generally regarded as safe (GRAS). Bac-D™ has been effectively used as a human first aid antiseptic for many years. The objectives of this trial were to determine the effects of Bac-D™ on egg conductance, hatchability, body weight and feed conversion (FC) in turkey eggs and poults. Turkey eggs were washed with Bac-D™ then incubated under standard conditions while recording egg conductance and hatchability. Body weights were measured at hatch, 21d and 42d. The results showed that egg conductance, hatchability, or body weights of chicks hatched from Bac-D™ washed eggs did not differ significantly from water washed controls. However, mean feed conversion was significantly lower (p